1998
DOI: 10.1046/j.1432-1327.1998.2540620.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of vitamin B12 in anaerobic bacteria

Abstract: In anaerobic bacteria 5-hydroxybenzimidazole and 5-hydroxy-6-methylbenzimidazole are precursors of the 5,6-dimethylbenzimidazole moiety of vitamin B 12 . In order to elucidate the pathway from these bases to vitamin B 12, experiments on the transformation of 5-hydroxy-6-methylbenzimidazole, of 5-hydroxy-6-methylbenzimidazole-A-D-ribofuranoside, of 5-hydroxybenzimidazolylcobamide and of 5-hydroxy-6-methylbenzimidazolylcobamide into vitamin B 12 were carried out.The vitamin B 12 synthesized by the anaerobe Eubac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Defined co-culture studies reported by Drzyzga et al (61) provide evidence of such syntrophic interspecies hydrogen transfer from a Desulfovibrio species to the dehalorespirer Desulfitobacterium frappieri TCE1 during the conversion of PCE to cDCE (with lactate serving as the source of electrons and in the absence of sulfate, as in ANAS). Certain LGCs such as Eubacterium limosum (a major clone type in the ANAS I library) have been reported to generate cofactors including Vitamin B12 (62), which is required by D. ethenogenes strain 195 for dechlorination. Additional studies tracking biochemicals (H2, B12, and organic acids) and employing selective physiological inhibitors will help elucidate how populations interact.…”
Section: Discussionmentioning
confidence: 99%
“…Defined co-culture studies reported by Drzyzga et al (61) provide evidence of such syntrophic interspecies hydrogen transfer from a Desulfovibrio species to the dehalorespirer Desulfitobacterium frappieri TCE1 during the conversion of PCE to cDCE (with lactate serving as the source of electrons and in the absence of sulfate, as in ANAS). Certain LGCs such as Eubacterium limosum (a major clone type in the ANAS I library) have been reported to generate cofactors including Vitamin B12 (62), which is required by D. ethenogenes strain 195 for dechlorination. Additional studies tracking biochemicals (H2, B12, and organic acids) and employing selective physiological inhibitors will help elucidate how populations interact.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, even though DMB is a symmetric molecule, the nucleotide loop is attached specifically through the nitrogen atom derived from glutamine (58,60). This puzzling result was justified by the hypothesis that an asymmetric intermediate from benzimidazole biosynthesis must undergo regiospecific phosphoribosylation, and the resulting intermediate would be a substrate for subsequent methylations (12,14,61). Because the M. thermoacetica bza operon produces the asymmetric benzimidazoles 5-OHBza and 5-OMeBza, the activities of the MtCobT and MtBzaC provided significant insights into this long-standing puzzle.…”
Section: Discussionmentioning
confidence: 99%